Un/tangling the skeins of History: Los amos del Valle, by Francisco Herrera Luque - Harringhton, María Susana (2018)
This article aims to analyze intertextuality as a discursive procedure in the rewriting of historiographic discourse in the novel Los amos del valle (1979), of the Venezuelan writer Francisco Herrera Luque. It is established that the work is constructed from an intricate web of texts that covers the author's literary and scientific production (intratextuality), as well as oral and written sources (extratextuality). Such composition constitutes a dialogue aimed at inciting plural readings of the Venezuelan reality, its historical representation and, even, the literary recreation itself, so that the narration updates and stimulates knowledge, which accounts for the cultural nuances. Thus, it is concluded that the articulation of the plot allows the reader to unravel the process of writing the historiographical discourse, in relation to the times of the conquest of the Province of Venezuela and its impact on the future of the country from then until today.